The role of CDPKs in plant development, nutrient and stress signaling - Dekomah, Simon Dontoro; Bi, Zhenzhen; Dormatey, Richard; Wang, Yihao; Haider, Fasih Ullah; Sun, Chao; Yao, Panfeng; Bai, Jiangping (Frontiers in Genetics, 2022)
The second messenger calcium (Ca2+) is a ubiquitous intracellular signaling molecule found in eukaryotic cells. In plants, the multigene family of calcium-dependent protein kinases (CDPKs) plays an important role in regulating plant growth, development, and stress tolerance. CDPKs sense changes in intracellular Ca2+ concentration and translate them into phosphorylation events that initiate downstream signaling processes. Several functional and expression studies on different CDPKs and their encoding genes have confirmed their multifunctional role in stress. Here, we provide an overview of the signal transduction mechanisms and functional roles of CDPKs. This review includes details on the regulation of secondary metabolites, nutrient uptake, regulation of flower development, hormonal regulation, and biotic and abiotic stress responses.